THE PRINCIPLE OF NON-DISCRIMINATION AS A FORM OF PROTECTION FOR UNDERAGE CHILDREN VICTIMS OF NARCOTICS AND PSYCHOTROPIC CRIMES - Ida Ayu Rosida; Rifda Ayu Akmaliya; Sonia Amelia; Ega Permatadani; Anang Dony Irawan (Universitas Muhammadiyah Tangerang, 2023)
The specific crime of narcotics is still something to be feared in Indonesia, the victims resulting from this problem are children. Even though the next generation of the nation are children who are in the growth stage, namely as survival assets for humans, the nation and the state. External and internal impacts are the cause of children who are victims of this evil object. Children have rights in their hands, with this right, children need to have legal protection, which has the goal of guaranteeing a child will get a decent life. Narcotics itself has been regulated in general, this is explained by the presence of Law no. 35 of 2009 concerning Narcotics. Rehabilitation efforts as well as special rules that clearly regulate juvenile justice are explained in law number 11 of 2012. On this occasion the author would like to discuss the Rehabilitation and Legal Protection of Underage Narcotics Crimes. The method used in this writing is normative legal research with a statutory and literature study approach which is then analyzed using qualitative method techniques using primary legal sources in the form of laws and regulations, secondary legal sources, namely from journals related to research and also legal sources. or or other legal sources. tertiary. From this paper it is hoped that it can provide knowledge about rehabilitation efforts for children who are caught in narcotics crime cases. The method used in this writing is normative legal research with a statutory and literature study approach which is then analyzed using qualitative method techniques using primary legal sources in the form of laws and regulations, secondary legal sources, namely from journals related to research and also sources or or other legal sources. tertiary. From this paper it is hoped that it can provide knowledge about rehabilitation efforts for children who are caught in narcotics crime cases. The method used in this writing is normative legal research with a statutory and literature study approach which is then analyzed using qualitative method techniques using primary legal sources in the form of laws and regulations, secondary legal sources, namely from journals related to research and also sources or or other legal sources. tertiary. From this paper it is hoped that it can provide knowledge about rehabilitation efforts for children who are caught in narcotics crime cases. secondary legal sources, namely from journals related to research and also other legal sources or sources. tertiary. From this paper it is hoped that it can provide knowledge about rehabilitation efforts for children who are caught in narcotics crime cases. secondary legal sources, namely from journals related to research and also other legal sources or sources. tertiary. From this paper it is hoped that it can provide knowledge about rehabilitation efforts for children who are caught in narcotics crime cases. Keywords: Children, Narcotics, Victims, Principles of Non-Discrimination, Rehabilitation.